A Parametric Study of Torrefaction Technology of Agricultural Residues in Indonesia - Andini, Ade; Arfiana; Finalis, Era Restu; Fausiah; Tjahjono, Endro Wahju; Saleh, Muksin; Iman; Firmandoko, Bagus Alif; Nuswantoro, Dorit Bayu Islam; Destian, Erbert Ferdy; Bangun, Herson; Sutriyanto, Himawan; et al. (Majalah Ilmiah Pengkajian Industri; Journal of Industrial Research and Innovation, 2023)
Enhancing the value of biomass residues holds promise for mitigating open burning. However, biomass utilization as an energy feedstock encounters its own set of challenges owing to inherent properties. To address these concerns, torrefaction, an essential thermal pretreatment process for carbonaceous materials, emerges as a viable solution. In a laboratory experiment conducted in a static tube reactor, torrefaction was investigated at temperatures of 250°C for 45 minutes and 300°C for 5 minutes. The findings revealed that rice straw, corncob, and cassava stalk exhibit properties exceptionally suited for utilization as energy feedstock. Notably, at 300°C corncob attains a carbon content of 58.10%, a fixed carbon content of 34.35%, and a calorific value of 22.46 MJ/kg.